Platelet‐Rich Plasma Increases Growth and Motility of Adipose Tissue‐Derived Mesenchymal Stem Cells and Controls Adipocyte Secretory Function. Issue 10 (October 2015) - D'Esposito, Vittoria; Passaretti, Federica; Perruolo, Giuseppe; Ambrosio, Maria Rosaria; Valentino, Rossella; Oriente, Francesco; Raciti, Gregory A.; Nigro, Cecilia; Miele, Claudia; Sammartino, Gilberto; Beguinot, Francesco; Formisano, Pietro
ABSTRACT Adipose tissue‐derived mesenchymal stem cells (Ad‐MSC) and platelet derivatives have been used alone or in combination to achieve regeneration of injured tissues. We have tested the effect of platelet‐rich plasma (PRP) on Ad‐MSC and adipocyte function. PRP increased Ad‐MSC viability, proliferation rate and G1‐S cell cycle progression, by at least 7‐, 2‐, and 2.2‐fold, respectively, and reduced caspase 3 cleavage. Higher PRP concentrations or PRPs derived from individuals with higher platelet counts were more effective in increasing Ad‐MSC growth. PRP also accelerated cell migration by at least 1.5‐fold. However, PRP did not significantly affect mature adipocyte viability, differentiation and expression levels of PPAR‐γ and AP‐2 mRNAs, while it increased leptin production by 3.5‐fold. Interestingly, PRP treatment of mature adipocytes also enhanced the release of Interleukin (IL)‐6, IL‐8, IL‐10, Interferon‐γ, and Vascular Endothelial Growth Factor. Thus, data are consistent with a stimulatory effect of platelet derivatives on Ad‐MSC growth and motility. Moreover, PRP did not reduce mature adipocyte survival and increased the release of pro‐angiogenic factors, which may facilitate tissue regeneration processes. © 2015 The Authors. Journal of Cellular Biochemistry Published by Wiley Periodicals, Inc. J. Cell. Biochem. 116: 2408–2418, 2015. © 2015 The Authors. Journal of Cellular Biochemistry Published by Wiley Periodicals, Inc.